Large patent ductus arteriosus in an adult complicated by pulmonary endarteritis and embolic lung abscess - Navaratnarajah, Manoraj (PAGEPress Publications, 2011)
Patent ductus arteriosus in the adult is an extremely rare clinical phenomenon. We report the case of a 34-year old man who developed pulmonary endarteritis and subsequent embolic lung abscess secondary to a large patent ductus arteriosus. This brief report also provides an overview of the natural history, potential complications, optimal therapy, and diagnostic dilemmas associated with this persistent congenital cardiac defect in adults.